War stories remembering Pearl Harbor, Dec. 7, 1941 - Newman, Edwin; Carroll, Jon. ([s.l.] : Atlas Video, 1991)
The War stories reveals the true essence of the Second World War, viewers see the conflict through the eyes of combat veterans and others who tell of events that changed history
Music by Jon Carroll
Narrated by Edwin Newman
Keywords: Pearl Harbor (Hawaii), Attack on, 1941 -- Personal narratives, American